Environmental impact assessment of quarries in four municipalities in western part of Kosovo - Behxhet, Mustafa; Zeqir, Veselaj; Zeka, Hana; Hajdari, Avni (Macedonian Journal of Ecology and Environment, 2016)
Industry of quarry and its allied activities in Kosovo have significantly contributed infrastructural development (road construction, highway, bridges, etc.) and improving living standard during the last decade. On the other side, its negative impact in environment such as land degradation, air and water pollution, loss of biodiversity, health related issues, noise, and vibrations are present and often visible. This research was focused on analysing the impact of operators on land degradation, air and water quality and biodiversity (flora and fauna including natural and cultural heritage). Research was implemented to assess environmental impacts of quarries in four municipalities located in the western part of the Republic of Kosovo: Istog, Pejë, Deçan and Gjakova. Research area covered a territory of 1,822 km2 , or 16.71% of the territory of the Republic of Kosovo. In total, 16 quarries were identified, of which 13 were still active and 3 passive. The largest number of quarries operated in the municipality of Istog (6), followed by Deçani with 4, Peja with 3 and Gjakova with 3. Altogether, a quarry operation in the research area occupied an area of 41.56 ha. The research findings showed that the quarry operations had high negative impacts in the environment. Even the most of operators had environmental permits issued by the Kosovo Ministry of Environment and Spatial Planning; they mostly weren’t respecting the provisions stipulated in the law. Most of them didn`t use any environmental friendly technologies, while existing technology had no filters for air and water purification. Deforestation, dust generation, water, air and noise pollution followed by resource depletion and biodiversity loss were common threats associated with open quarry operations in the investigated area.